Flash Drive Authorization Using System Volume Information - Zaiddi, Ridzuan (Journal of Computing Technologies and Creative Content, 2019)
Flash Drive Authorization Using System Volume Information is a document encryption tool which is designed to secure access to the documents using rooted flash drive and protecting the documents by providing encryption. To securely access the documents, the system is using MD5 encryption algorithm to generate user’s credentials that later will be stored inside the rooted flash drive under folder system volume information whereas documents encryption will be using AES encryption algorithm. In addition, the combination of rooted flash drive that contains user’s credentials is needed in securing access to the documents. This means the authorized user has the legitimate access for authentication and only authorized user has the privilege to access the system which is to encrypt or decrypt the documents. In short, this project is using two encryption algorithms which are MD5 and AES to increase security.